Our library - Bunting, Eve, 1928-2023.; Smith, Maggie, 1965- (New York : Clarion Books, 2008)
A raccoon and his friends go to great lengths to make sure they will always have a library from which to borrow books.
Keywords: Libraries -- Fiction; Books and reading -- Fiction; Raccoon -- Fiction; Animals -- Fiction; Picture books for children; Libraries -- Juvenile fiction; Books and reading -- Juvenile fiction; Raccoon -- Juvenile fiction; Animals -- Juvenile fiction